(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Modern medicine does not have reliable liver protection drugs that prevent and treat liver injury caused by drugs. The leaves of sacred / holy basil (Ocimum sanctum) belong to the family of lamiaceae, which is traditionally used for its liver protection. We aimed to determine if Ocimum sanctum has hepatoprotective properties and, if so, whether or not they work synergistically with silymarin. Albino rats (150–200 g) were divided into five groups. Groups A and B are normal control groups and experimental control groups, respectively. Groups C, D and E received the alcoholic extract of Ocimum sanctum leaves (OSE) 200 mg / kg BW / day, silymarin 100 mg/kg BW/day and OSE 100 mg/kg BW/day + silymarin 50 mg/kg BW/day p.o., respectively, for 10 days. Hepatotoxicity was induced in Groups B, C, D and E on the eighth day with paracetamol 2 g/kg BW/day. The effect of hepatoprotection was evaluated through a study of serum proteins, albumin-globulin ratios, alkaline phosphatase, transaminase, and liver histology. The results of the study were presented as averages and standard deviations for each group (SEM). The study group was compared with the control group with a single-way ANOVA and Bonferoni test followed. A P-value of <0.01 was considered significant. In groups C, D and E, liver enzymes and albumin globulin ratio were significantly (P < 0.01) closer to normal than in group B. On histological inspection, groups C, D and E revealed reduced sinusoidal congestion, cloudy edoema, fatty abnormalities, and regenerating regions of the liver, but group B showed only liver necrosis. The extract of the alcoholic leaves of Ocimum sanctum has significant liver protection and synergy with Silimarin.